Parasite Carbohydrate Vaccines - Jaurigue, Jonnel A.; Seeberger, Peter H. (Frontiers in Cellular and Infection Microbiology, 2017)
Vaccination is an efficient means of combating infectious disease burden globally. However, routine vaccines for the world’s major human parasitic diseases do not yet exist. Vaccines based on carbohydrate antigens are a viable option for parasite vaccine development, given the proven success of carbohydrate vaccines to combat bacterial infections. We will review the key components of carbohydrate vaccines that have remained largely consistent since their inception, and the success of bacterial carbohydrate vaccines. We will then explore the latest developments for both traditional and non traditional carbohydrate vaccine approaches for three of the world’s major protozoan parasitic diseases – malaria, toxoplasmosis, and leishmaniasis. The traditional prophylactic carbohydrate vaccine strategy is being explored for malaria. However, given that parasite disease biology is complex and often arises from host immune responses to parasite antigens, carbohydrate vaccines against deleterious immune responses in host-parasite interactions are also being explored. In particular, the highly abundant glycosylphosphatidylinositol molecules specific for Plasmodium, Toxoplasma and Leishmania spp. are considered exploitable antigens for this non-traditional vaccine approach. Discussion will revolve around the application of these protozoan carbohydrate antigens for vaccines currently in preclinical development.